Protective effect and mechanism of ginsenoside Rg1 in cerebral ischaemia-reperfusion injury in mice - Wang, Le; Zhao, Hong; Zhai, Zhen-zhen; Qu, Li-xin (Biomedicine & pharmacotherapy, 2018)
Ginsenoside Rg1 is regarded as one of main bioactive compounds responsible for pharmaceutical actions of ginseng with little toxicity and has been shown to have possibly neuroprotective effects. However, the mechanism of its neuroprotection for acute ischemic stroke is still elusive. The purpose of present study is thus to assess the neuroprotective effects of the ginsenoside Rg1 against neurological injury in a mice model of cerebral ischemia/reperfusion (I/R), and then to explore the mechanisms for these neuroprotective effects. Mices were pretreated with ginsenoside Rg1 20,40 mg kg−1 d−1, ig, for 7d, respectively, then subjected to cerebral ischenmia (middle cerebral artery occlusion) for 2 h and reperfusion for 22 h. The infarct volume and the neurological deficit were determined by TTC staining and Longa′s scoring, respectively. The protein expression of brain-derived neurotrophic factor (BDNF) was analyzed by Immunohistochemistry and Western blot, respectively. Interleukin-1β (IL-1β), tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) expression in serum was measured by ELISA kit. High-performance liquid chromatography (HPLC) was used to explore the contents of Glu and Asp. Compared with the ischemia/reperfusion group, ginsenoside Rg1 40 mg/kg group has significantly reduced infarct volume, neurological deficit scores (P < .05), Interleukin-1β (IL-1β), tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) contents in serum (p < .01, respectively), the contents of Glu and Asp (P < .01). Immunohistochemistry and Western blot indicated that ginsenoside Rg1 40 mg/kg group significantly increased brain-derived neurotrophic factor (BDNF) protein expression in the CA1 regions of the hippocampus (p < .01). Ginsenoside Rg1 40 mg/kg has protective effects on cerebral injury induced by ischeamia/reperfusion, which might be related to the increased in the expression of BDNF in the hippocampal CA1 region, the down-regulation of the expression of IL-1β、IL-6 and TNF-α in serum, the decreases in the contents of Glu and Asp in the brain tissue.